DEVELOPMENT STRATEGIES OF PHARMACEUTICAL INDUSTRY IN ACCORDANCE WITH THE HEALTHCARE NEEDS IN RUSSIA - V. Makhalin; P. Kostromin (Вестник университета, 2016)
In the article current state of the Russian pharmaceutical industry, the pharmaceutical market and import of medicines to Russia regarding their compliance to the purposes and tasks set in industry strategic documents of development, and also to requirements of health care of the country is analysed. Extent of saturation of the market by the Russian medicines and consequences of the external economic sanctions for provision of medicines of the population of the country is defined. Conclusions are drawn on the reasons of discrepancy of the current situation in the Russian pharmaceutical industry for the plans declared by the state and the priority directions of their decision are designated.